Longitudinal relationship between adverse childhood experiences and depressive symptoms: the mediating role of physical pain - Min Bao; Rongji Ma (BMC Psychiatry)
Abstract Background This study explored the relationship between Adverse Childhood Experiences (ACE), physical pain, and depressive symptoms, and examined the mediating role of pain in the correlation between ACE and depressive symptoms among middle-aged and elderly Chinese (over the age of 45). Methods Cox proportional hazards regression models were used to analysis the association between ACE, physical pain, and depressive symptoms. To assess the mediating role of physical pain in the relationship between ACE and depressive symptoms, mediation analysis was conducted. Indirect, direct, and total effects were estimated by combining mediation and outcome models, adjusting for relevant covariates. Bayesian network models were used to visually demonstrate the interrelations between factors influencing depressive symptoms, further verifying the association between ACE, physical pain, and depressive symptoms. Results In the fully adjusted model, middle-aged and elderly individuals reporting ACE had a higher risk of developing depressive symptoms (hazard ratios [HR] and 95% confidence intervals [95% CI], 1.379 [1.266–1.503]). Compared to those without physical pain, individuals reporting severe physical pain were at an increased risk of depressive symptoms (HR [95% CI], 1.438 [1.235–1.673]). The risk was even higher for those with both ACE and severe physical pain compared to those with neither (HR [95% CI], 2.020 [1.630–2.505]). The intensity of pain explained 7.48% of the association between ACE and depressive symptoms, while the number of pain sites accounted for 7.86%. Conclusions Physical pain partially mediated the association between ACE and depressive symptoms. The study findings highlighted the importance of early screening and intervention for physical pain in middle-aged and older adults with ACE. Clinical trial number Not applicable.